Kulturraum Österreich Die Identität der Regionen in der bildenden Kunst des 19. Jahrhunderts - Telesko, Werner (2008)
While the first volume of the overalll work, which was published as "The historical Area of Austria" ("Geschichtsraum Österreich") in 2006, focused on the Hapsburgian "whole state" from the perspective of the most important phenomena and protagonists of the "Hapsburgian iconography", this second and concluding volume examines multifarious visualisations of the regional and supraregional historical myths of the 19th century in Vienna, the "centre", and in the regions, i.e. the Austrian Crownlands (part of which are identical with today´s federal provinces of the Republic of Austria). The difficult relationship between the "whole state" and the Crownlands constitutes the entire, extremely complex spectrum of reflections on Austrian 19th century history. Here, the kinds of methods and concrete goals with which regional memorial foundations interact or compete with dynastic strategies is a pivotal issue - on that has been examined only far too rarely in the past. Hence the present work intends to discuss both art-historical and historical phenomena with explore various historical reflections at the - frequently neglected - "periphery" and investigate visual approaches to one´s "own" history from the "present" of the 19th century (using prominent events such as the second Ottoman siege of 1683 and the "wars of liberation" against Napoleon as an example). The degrees of complexity, quantitative permeation and significant contrasts between Vienna - the "centre" - and the "provinces" in their different reflections on Austrian history clearly begin to emerge when we examine an extensive range of topics against the background of competing national, regional and communal strategies. Compared to the first volume "The historical Area of Austria", the perspective of the multifarious "historical area of Austria" shifts from the "whole state" to an analysis of a highly distinct "plurality of areas" (Karl Schlögel) with its own intrinsic laws. Such diversity is also an essential factor when we come to investigate the prolific amount of Austrian landscape art in the 19th century and the role it played in forging identity. It graphically demonstrates that a deeper understanding of Austria´s federal structures is not possible without gaining a comprehensive insight into 19th century history.